A survey of Japanese policy on Islam and Muslim community in Malaya, 1941-1945 - Mansor Majdin, Mohamad Firdaus; Fathil, Fauziah (Global Academic Excellence (GAE), 2017)
Japanese occupation of Malaya is considered to be a departure point in Malaysian history which marked a shift of colonial rule from British to Japanese. In the context of Malaya, following the successful Japanese subjugation of the land in February 1942, the High Command in Tokyo had issued a number of directives to be implemented in the occupied areas including Malaya. The High Command in Tokyo, among others had specified that regional commanders need to respect the indigenous’ religion and folk customs in the occupied areas. As far as Islam is concerned, the Japanese Military Administration in Malaya seemed to have departed from Tokyo’s orders in its dealing with Islam and Malay-Muslims as a whole. It seemed that the Japanese had no well-planned policy on Islam and Malay-Muslims in Malaya, nor were they sensitive to Islam and relevant issues concerning Islam and Muslims in the country. Rather Islam was used for propaganda purposes such as the frequent presence of Japanese officials in surau or mosque precincts for mobilizing people’s support and occasional use of surau or mosques as storehouses.